Hope and Crisis in McCarthy’s The Road and Mandel’s Station Eleven - Sharma, Prakash (Intellectual Inception: A Multidisciplinary Research Journal of Bhojpur Campus, 2024)
Presentation of the duality of hope and crisis for eco-conscious is the main feature of post-apocalyptic fictions. This research work comparatively analyzes the revelation of hope and crisis in Cormac McCarthy’s The Road and Emily St. John Mandel’s Station Eleven from ecocritical perspective. These fictional works expose extreme destruction of life, property and even the natural world.Human beings interfere in the course of nature, by violating the web of interdependence between plants and animals and neglecting its autonomous existence. These novels reveal the germination of the different types of apocalypses because of such invasion, which ultimately push our ecosphere in danger.Such displays of the dystopian worlds are purposeful. They aim to strike the thoughts of people and make them serious towards ecological issues. They give the sense of imminent environmental peril to correct their misdeeds. At the same time, such fictional works also include events and situations that signal optimism in the readers. The comparative study reveals that the key point of the post-apocalyptic fictions is to present the dialectics of hope and hopelessness for the eco-conscious in readers and make them ecofriendly.This paper follows qualitative research design focusing on the textual analysis method for the analysis of the primary texts to justify the claim. Critical ideas of Lawrence Buell in relation to the environmental apocalypse are used as analytical tools for critical analysis.